Föränderliga stadsrum - Andersson, Jenny; Gustafsson, Anna (2008)
The number of inhabitants of the towns and city centers have generelly increased, concurrent as the population in smaller towns has decreased. In Stockholm, the migration is very fast and here is also the most populous place, if one compares with other Sweden.